2015
DOI: 10.1021/acs.analchem.5b03772
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Microfluidic System for Size-Based Selection and Trapping of Giant Vesicles

Abstract: Vesicles composed of phospholipids (liposomes) have attracted interest as artificial cell models and have been widely studied to explore lipid-lipid and lipid-protein interactions. However, the size dispersity of liposomes prepared by conventional methods was a major problem that inhibited their use in high-throughput analyses based on monodisperse liposomes. In this study, we developed an integrative microfluidic device that enables both the size-based selection and trapping of liposomes. This device consists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 36 publications
0
48
2
Order By: Relevance
“…[28,43,78,79] For the bottom-up creation of artificial cells, having a monodisperse population may be advantageous for making repeat observations of morphological changes or to control the rates of encapsulated enzymatic reactions. [28,43,78,79] For the bottom-up creation of artificial cells, having a monodisperse population may be advantageous for making repeat observations of morphological changes or to control the rates of encapsulated enzymatic reactions.…”
Section: Microfluidic Methods For Size-based Selection Of Giant Vesiclesmentioning
confidence: 99%
See 4 more Smart Citations
“…[28,43,78,79] For the bottom-up creation of artificial cells, having a monodisperse population may be advantageous for making repeat observations of morphological changes or to control the rates of encapsulated enzymatic reactions. [28,43,78,79] For the bottom-up creation of artificial cells, having a monodisperse population may be advantageous for making repeat observations of morphological changes or to control the rates of encapsulated enzymatic reactions.…”
Section: Microfluidic Methods For Size-based Selection Of Giant Vesiclesmentioning
confidence: 99%
“…[28,43,78,79] For the bottom-up creation of artificial cells, having a monodisperse population may be advantageous for making repeat observations of morphological changes or to control the rates of encapsulated enzymatic reactions. [29,78] Storslett and Muller showed that inertial focusing can be used to sort different vesicle populations into different outlet channels. On-chip size selection can either be achieved using trapping posts and changing the height of microchannels [28] or by filtering the GUVs based on their behavior in different flows.…”
Section: Microfluidic Methods For Size-based Selection Of Giant Vesiclesmentioning
confidence: 99%
See 3 more Smart Citations